Annual Review of Pharmacology and Toxicology. (Annual Reviews Inc, 1981)
Prefatory chapter. Mechanisms of action of drugs and chemicals. Structure-Activity relationships and medicinal chemistry. Pharmacokinetics, drug absorption, and excretion. Cancer chemotherapy and immunopharmacology. Neuropharmacology and neurochemist.